A single-beam NIR laser-triggered full-color upconversion tuning of a Er/Tm:CsYb2F7@glass photothermal nanocomposite for optical security. Issue 9 (17th February 2022) - Zhu, Jiwen; Wang, Shaoxiong; Yang, Zezhong; Liao, Shengxiang; Lin, Jidong; Yao, Hurong; Huang, Feng; Zheng, Yuanhui; Chen, Daqin
Abstract : The development of advanced luminescent materials is highly desirable for addressing the rising threat of forgery. Abstract : The development of advanced luminescent materials is highly desirable for addressing the rising threat of forgery. However, it is challenging to achieve stable full-color upconversion (UC) tuning in the same matrix upon a single-beam light excitation so as to ensure that authentic items are irreproducible. Herein, hexagonal Er/Tm:CsYb2 F7 nanocrystals (NCs) embedded inorganic glass via an in situ crystallization strategy is fabricated, which can emit blue, cyan, green, yellow, orange, red and near-infrared (NIR) UC emissions by simply modifying an incident 980 nm laser power. This UC tuning is attributed to the combination roles of the highly efficient laser-induced photothermal effect of the CsYb2 F7 host and simultaneous emissions of Er and Tm activators. Importantly, the robust inorganic glass matrix endows Er/Tm:CsYb2 F7 NCs with excellent water resistance and the ability to withstand high-power laser irradiation. Based on these unique characteristics, a proof-of-concept anti-counterfeiting experiment is designed. The results indicate that dynamic full-color UC luminescence patterns can be easily tuned by simply changing the power of the incident 980 nm laser. The present work not only confirms that the designed photothermal material can increase information security, but also provides a new idea for practical applications in the field of anti-counterfeiting.